Long-Term Survival of Adult Patients With Atrial Septal Defect With Regards to Defect Closure and Pulmonary Hypertension - Rubáčková Popelová, Jana; Tomková, Markéta; Tomek, Jakub; Živná, Renata (Frontiers in cardiovascular medicine, 2022)
BACKGROUND: Atrial septal defect (ASD) is the most common congenital heart disease (CHD) in adults and pulmonary hypertension (PH) is an established risk factor. A decision whether to perform ASD closure, especially in elderly patients with PH, is a complex dilemma. The aim of our study was to compare long-term survival in patients with closed and open ASD. METHODS: A retrospective cohort study was performed on 427 patients with ASD (median age at diagnosis 38 years, IQR 18-56) out of which 186 patients (44%) manifested PH. ASD closure in patients with PH was only considered in patients without Eisenmenger syndrome with pulmonary vascular resistance < 5 WU. Median follow-up duration was 18 years (IQR 9-31 years). Kaplan-Meier and Cox proportional hazards survival analyses were performed to evaluate 12 potential predictors of survival. RESULTS: Defect closure was associated with improved long-term survival in ASD patients both with (P < 0.001) and without PH (P = 0.01) and this association was present also in patients over 40 years. The 20-year survival since diagnosis was significantly higher in patients with PH and closed ASD compared to those with PH and open ASD (65% vs. 41%). ASD closure was a significant independent predictor of long-term survival (P = 0.003) after accounting for age at diagnosis, PH, NYHA class, Eisenmenger syndrome, and mitral regurgitation. Significant negative independent predictors of survival were older age at diagnosis (P < 0.001), Eisenmenger syndrome (P < 0.001), and PH (P = 0.03). CONCLUSION: ASD closure appears to be associated with improved long-term survival independently of age, PH, and other clinical variables.
Keywords: atrial septal defect; long-term survival; congenital heart disease; pulmonary hypertension; defect closure